Mathematics Mobility in the Middle Grades: Tracking the Odds of Completing Calculus - Kristian Edosomwan; Jamaal Young; Jemimah Young; Alana Tholen (Middle Grades Review, 2022)
High school calculus has become indispensable for students seeking a college degree in a STEM field. However, in the present study, we argue that the mathematics opportunities that students seize (when afforded) in middle grades are the key to earning calculus credit in high school. To take calculus in high school, students usually need to take advanced mathematics in middle school to take the prerequisite courses. We analyzed the probability of earning credit in calculus based on a sample of (n =17,765) students and their eighth-grade mathematics courses. Using descriptive statistics and odds ratio effect sizes we found that taking advanced (i.e., algebra in eighth grade) mathematics courses greatly increased a student's chances of earning calculus credit in high school. However, the results indicated that taking double advanced (i.e., geometry in eighth grade) only statistically significantly improved the odds of Asian students earning calculus credit in high school. While participating in double advanced mathematics statistically significantly lowered the odds of earning calculus credit compared to the advanced track for Black and Latinx students. These findings have major implications for providing equitable math instruction for all students, especially in light of the many math students who are tracked into courses with limited ways to earn the calculus credit necessary for STEM-related college and career success.
Keywords: mathematics; tracking; calculus; middle school; algebra